Analysis of the Implementation of PSAK No. 18 Pension Fund Accounting Reporting at BPJS Ketenagakerjaan Meulaboh Branch - Wardani, Kiki; Firman, Cut (Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to analyze the accounting recording of pension funds applied by the Meulaboh branch of BPJS Ketenagakerjaan based on the Statement of Financial Accounting Standards (PSAK) No. 18. The type of research used in this research is quantitative comparative. Data collection used in this research is by means of observation, interviews, and documentation. The analysis technique used in this research is comparative descriptive analysis, namely comparing the Meulaboh branch of the BPJS Ketenagakerjaan pension fund report with the Statement of Financial Accounting Standards (PSAK) No. 18. The results of this study indicate that the net asset and contribution reports have been presented in accordance with PSAK No. 18, but the fund management report has not used fair value in investment management, as stipulated in PSAK No. 18.